Opportunities and Objections in the Iraq Development Road Project: A Focus on Erbil-Baghdad Disputes in a Federal Framework - Koc, Engin (Journal of Legal and Political Studies, 2025)
The Iraq Development Road Project (IDRP), envisioned as a transformative trade corridor connecting the Gulf to Iraq’s northern borders and beyond, has immense potential to strengthen Iraq’s economic connectivity and diversify its economy. However, the project's success hinges on overcoming disputes between the Kurdistan Regional Government (KRG) in Erbil and the federal government in Baghdad. These disputes, rooted in Iraq’s federal structure, revolve around legislative authority, administrative powers, and revenue sharing, which are critical to the project's implementation and sustainability. This study examines the IDRP through the lens of federalism, focusing on key legal and administrative challenges that arise from the differing perspectives of the KRG and Baghdad. It explores the legislative framework governing the project, disputes over resource control, and the allocation of administrative powers between regional and federal authorities. These issues highlight how unresolved legal ambiguities and political tensions impede progress and threaten Iraq’s broader development goals. The findings reveal that addressing these disputes requires a clear legal framework to regulate the roles and responsibilities of regional and federal authorities. Furthermore, the study emphasizes the importance of administrative reform and enhanced cooperation to ensure the project aligns with Iraq’s constitutional principles and achieves its intended goals. This research aligns with the academic themes of the role of federalism in resolving disputes between regional and federal authorities. It underscores the IDRP’s potential to foster national unity and strengthen Iraq’s federal structure if its challenges are addressed collaboratively. Key Words: Iraq, KRG, Iraq Development Road Project, Erbil-Baghdad Disputes, Federalism
Keywords: Iraq; KRG; Iraq Development Road Project; ErbilBaghdad Disputes; Federalism